THE DEVELOPMENT OF DISCOVERY LEARNING BASED SCIENCE WORKSHEETS WITH CRITICAL THINKING SKILLS ORIENTATION FOR THE TOPIC OF SOLAR SYSTEM - Billa, Salsa; Sari, Monica Prima (Universe, 2025)
Based on the results of observations made in several schools, it was found that learning in schools was still dominant using the lecture method and lack of teaching materials in the form of worksheets for learning. This research study aims to determine the validity and practicality of Integrated Science Worksheets based on discovery learning models in the solar system. This research is a Research and Development (R&D) research with a 4D development model. The instruments used in this study were observation questionnaires, validity questionnaires, and practicality questionnaires. The learning worksheet is validated by an expert validator using a validity questionnaire. The practicality test was carried out by teachers and students using a practicality questionnaire. Based on data analysis, product validity and practicality with an average validity of 0.90 are in the very high category. The practicality average value of using integrated science worksheets based on the discovery learning model according to the teacher and students respectively is 0.89 and 0.92 which is included in the very high category. So it can be concluded that the integrated science worksheet based on the discovery learning model in the solar system is valid and practical to use.